2021
DOI: 10.5812/jhealthscope.108482
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Tourism Industry in Iran: A Review of Websites Designed for Cross-border Patients

Abstract: Background: Cross-border health care, whether sanctioned by the governments (out-of-country care) or initiated by the patients (medical tourism), is on the rise globally. The medical tourism industry has shown great potential for improvement in Iran. Objectives: We aimed to examine the representation of data elements on Iranian public and private medical tourism websites and evaluate their content maturity. Methods: A descriptive cross-sectional design was used to gather and statistically analyze data from 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, according to our findings, while all ownership types of the hospitals had low-quality content, public hospitals had lower quality scores than semi-private and private hospitals. Similarly, a study by Baghbanian et al showed that among the medical tourism websites, the websites of private organizations scored better [25]. This may be because private sector hospitals do not receive a governmental budget and are fully responsible for their financing, so they attract more foreign patients through their IPD websites than public sector hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to our findings, while all ownership types of the hospitals had low-quality content, public hospitals had lower quality scores than semi-private and private hospitals. Similarly, a study by Baghbanian et al showed that among the medical tourism websites, the websites of private organizations scored better [25]. This may be because private sector hospitals do not receive a governmental budget and are fully responsible for their financing, so they attract more foreign patients through their IPD websites than public sector hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the average state of data display, most of the private websites and only one government website was in an average state. In the end, they concluded that for the development of medical tourism; In addition to political and economic issues, the development of technological and communication infrastructures to promote this industry should be considered [20].…”
Section: Baghbanian Et Al Conducted a Cross-sectional Study On Iran's...mentioning
confidence: 99%
“…Today, cultural diversity has increased in the context of health care due to globalization (Van Oudenhoven et al, 2006). Medical tourism has increased dramatically in Iran (Baghbanian, Safdari, Erfannia, & Zokaee, 2021;Rahimi Zarchi et al, 2018), and this country's medical tourism industry is expected to develop rapidly (Baghbanian et al, 2021). This could make IC between doctors and patients from other countries and cultural backgrounds inevitable in Iran's hospitals.…”
Section: Ic In Healthcarementioning
confidence: 99%